2016
DOI: 10.1051/0004-6361/201527377
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV eBOSS emission-line galaxy pilot survey

Abstract: The Sloan Digital Sky Survey IV extended Baryonic Oscillation Spectroscopic Survey (SDSS-IV/eBOSS) will observe 195 000 emission-line galaxies (ELGs) to measure the baryonic acoustic oscillation (BAO) standard ruler at redshift 0.9. To test different ELG selection algorithms, 9000 spectra were observed with the SDSS spectrograph as a pilot survey based on data from several imaging surveys. First, using visual inspection and redshift quality flags, we show that the automated spectroscopic redshifts assigned by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 51 publications
(64 reference statements)
1
34
0
Order By: Relevance
“…For the type 1 AGNs, there exist a large number of optical spectra, and the stacking method permits the construction of high-quality stacks that are almost noise free, see Fig B1. For the type 2 AGNs, the number of available spectra is small, so that the stacks have noise, in particular at redshift higher than 1, see Fig B2. For the type 3 AGNs, we use the elliptical, red galaxy spectrum model, see Fig B3. To construct galaxy archetypes we use SDSS spectra as selected in (Abazajian et al 2009;Dawson et al 2013;Prakash et al 2016) for the elliptical galaxies ( Fig B3) and as in (Comparat et al 2013(Comparat et al , 2016Raichoor et al 2017) for the star-forming galaxies ( Fig B4).…”
Section: Optical Medium Resolution Spectramentioning
confidence: 99%
“…For the type 1 AGNs, there exist a large number of optical spectra, and the stacking method permits the construction of high-quality stacks that are almost noise free, see Fig B1. For the type 2 AGNs, the number of available spectra is small, so that the stacks have noise, in particular at redshift higher than 1, see Fig B2. For the type 3 AGNs, we use the elliptical, red galaxy spectrum model, see Fig B3. To construct galaxy archetypes we use SDSS spectra as selected in (Abazajian et al 2009;Dawson et al 2013;Prakash et al 2016) for the elliptical galaxies ( Fig B3) and as in (Comparat et al 2013(Comparat et al , 2016Raichoor et al 2017) for the star-forming galaxies ( Fig B4).…”
Section: Optical Medium Resolution Spectramentioning
confidence: 99%
“…Though pilot surveys demonstrated that a target selection based on the SDSS imaging passed the eBOSS requirements (Comparat et al 2016a;Raichoor et al 2016;Delubac et al 2017), the deep grz-band photometry of the Dark Energy Camera Legacy Survey (DECaLS 15 ) enables a more efficient target selection. Thus, the eBOSS ELG target selection ) has been done on the DECaLS grz-band photometry.…”
Section: Eboss Elg Samplementioning
confidence: 99%
“…The number of observed high-redshift star-forming galaxies with emission line measurements is growing quickly with recent optical and near-infrared surveys (see e.g., Comparat et al 2016a;Okada et al 2016;Delubac et al 2017;Kaasinen et al 2017;Drinkwater et al 2018). But the sample sizes of the current ELG surveys are still not large enough to fully understand the properties of the high-redshift ELGs.…”
Section: Introductionmentioning
confidence: 99%
“…These surveys use the Sloan Foundation 2.5m Telescope at Apache Point Observatory (Gunn et al 2006), and the BOSS spectrograph, which covers the wavelength range of 360 ∼ 1000 nm with 1000 fibers per 7-deg 2 plate at a resolution of R ∼ 2000 (Smee et al 2013). The ELG target selection is based on grz-band photometry (Comparat et al 2016;Raichoor et al 2017) (Comparat et al 2013. The ELG survey covers an area of ∼ 620 deg 2 in the Southern Galactic Cap (SGC) and ∼ 600 deg 2 in the Northern Galactic Cap (NGC) at a target density of 200 deg −2 in the NGC and 240 deg −2 in the SGC, respectively.…”
Section: Eboss Survey and Elg Samplementioning
confidence: 99%